Teia da vida: processos e produção de tecnologias educacionais numa perspectiva da complexidade para criação de web currículos - Barreto, Gilson Oliveira (2015)
perspective of the complexity for creating web curricula is carried out from the project Teia da Vida - developed at the Universidade Federal de Goiás by Laboratório de Tecnologia da Informação e Mídias Educacionais, which was dedicated between the years 2007-2010 to the production of digital content in biology for high school. The focus of this study covers the steps occurred during the production processes constituted by moments of reflections about the action, workshops, experiments, ideas production and products that involved high school students. The research goal is therefore to conduct a document analysis of processes and products, trying to identify an approach to the complex thinking. For this are made forty-one (41) intelligibility indicators of complexity based on the principles of complexity formulated by Edgar Morin, which form the basis for information and data analysis originated from interviews and products made by students. Of the forty-one (41) produced indicators, from the analysis were selected twenty-two (22) and from the metaanalysis made emerge two more (2). Finally, I show limits and possibilities of educational technology processes and productions from the perspective of activity and complex thinking pointing to creation of web curricula